Dealing with diversity in higher education: awareness-raising and a linguistic perspective on teachers' intercultural competence. Issue 3 (2nd July 2016) - Murray, Neil
Abstract : Higher education institutions around the world are educating an increasingly diverse student population. While this responds to government discourse around widening participation and the need to internationalise, and while it can make for a stimulating teaching-learning environment, it can also present teachers with certain challenges that demand greater intercultural competence. This article considers how, as part of their intercultural repertoire, teachers – and by extension, students – can benefit from developing an understanding of language, and, in particular, the general principles governing how we mean in language and the lingua-cultural variability that impacts upon the process of doing so. It proposes awareness-raising activities as a way of promoting such understanding.